PENGARUH PENERAPAN LKPD BERBASIS DISCOVERY LEARNING TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK KELAS XI IPA SMAN 1 TANJUNG MUTIARA - Windia Aprilia (Jurnal Edukasi dan Penelitian Matematika, 2021)
Understanding mathematical concepts is one of the goals that must be mastered by students in learning. The understanding of mathematical concepts of students in class XI IPA SMAN 1 Tanjung Mutiara is still low, because students have’nt actively involved in finding mathematical concepts. The solution to this problem is to use LKPD based on discovery learning. This type of research is a semi-test plan with a Static Gathering Plan. XI IPA 1 as the experiment class and the control class is XI IPA 2. The instrument in this research is a test of understanding mathematical concepts. The instrument of this research is the final test. The final test was analyzed using t-test. Based on the results of the analysis of students' understanding of mathematical concepts, the value of P = 0.001 is smaller than the level of significance = 0.05. So, the understanding of mathematical concepts of students who learn by using LKPD learning is better than the understanding of mathematical concepts of students who learn by using LKPD which is commonly used before. Keywords — Understanding mathematical concepts, Students worksheet, Discovery learning